KEGAGALAN YUNANI MEMANFAATKAN BAILOUT DALAM UPAYA MENGATASI KRISIS EKONOMI TAHUN 2008 - Pane, Boy Yusuf; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Most of the Europen countries has been cautiously observing the contraction of the Greek system which is closely tied to their own economies. It has capture the attention of the world and continued to send warning signs to countries about system of the governance and public finance. Thus, the case of the Greek crisis has been an good example of how bad management of public finances, Regional Institutions, and domestic politics condition can lead to an economic catastrophe. This research is aimed to explain the failure of Greece on overcoming the debt crisis and also its failure using the bailout aid from European Union.This research theoretically has built with rasionalism perspectives on International Relations and supported by Complex Interdepence theories, and also the concept of Diplomatic Bailout in International Politcal-economy. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Scope of this research is Greece’s Failure applying the bailout aid from European Union on overcoming its economic crisis.Researcher has formulated an answered-hypothesis which reveals the facts that Greece failure is caused by the complexity of the bailout itself. The complexity came from first, high level of financial interest of European Union to overcome its financial stability than the Greece financial interest itself. Second, the domestic politics condition in Greece and the third is the gap between intergovernmental aspects and national sovereignty within Euro-zone States after crisis.Keywords: European Crisis, Greece Debt Crisis, Greece, European Union, Bailout.